Effect Of Pruning And Fertilizer Application On The Quality Of Diospyros Melanoxylon Leaves In Chhattisgarh (India) (Applied Biological Research, 2020)
Tendu (Diospyros melanoxylon) leaf is used to wrap ‘Bidi’ or Indian  cigarette due to its texture, flavour and workability. Experiments were  conducted in tendu during 2015-2017 to assess the impact of pruning and  application on chemical- and bio-fertilizers on leaf quality of this plant in  Korba, Korea and Raipur districts of Chhattisgarh (India). Various levels  of nitrogen (25-100 kg N ha-1) and phosphorus (250-1000g plot-1), neem  granules, vesicular arbuscular mycorrhizal (VAM) and foliar spray of N  and P (0.5-2.0%) were tested in a factorial randomized block design experiment. Every year pruning of tendu bushes of 2-4 cm girth at ground  level increased the leaf surface area. Theapplication of 100 kg N ha-1 and  25 kg P ha-1to rhizosphere soil after rainy season improved tendu leaf  quality in terms of specific leaf area. Foliar spray of 2% N and 1% P on  tendu bushes enhanced leaf size and were more effective than chemical  fertilizer application to soil. Similarly, application of biofertilizers in the  form of 500 g neem granules and 1000 g VAM plot-1enhanced the leaf  quality of tendu.
Keywords: Biofertlizer; chemical fertilizers; Diospyros melanoxylon; foliar spray; neem; pruning; tendu